Accumulation of artificial and natural radionuclides in hydrobionts of the Konoplyanka River (Kamianske City, Dnipropetrovsk region) - N. Hudym (Ribogospodarsʹka Nauka Ukraïni)
Purpose. To determine the radiation state of the ecosystem in the technologically modified Konoplyanka River in the area of ​​radioactive waste tailings dump and the mouth of the river (at the siteof confluence with the Zaporizhzhya (Dnipro) Reservoir), by analyzing the coefficients of radionuclides accumulation of natural and artificial origin in hydrobionts.